Asya krizi ve Türkiye ekonomisine etkileri - Ersoy, Ertan (My University, 2001)
1970'lerin başlarından itibaren başlayan ekonomik durgunluk dünya ekonomisinde önemli yapısal değişikliklere neden olmuştur. Bu yapısal değişiklikler ekonomik aktiviteleri öncekinden daha serbest bir rejim altında yürütme gereğini doğurmuştur. Bu süreç bütün dünyada fianasal liberalizasyon ve finansal deregülasyona neden olmuştur. Gelişmekte olan ülkelerde fianasal liberalizasyon buralarda temel makroekonomik dengeler sağlanmadan yapılmıştır. Bu yüzden bu ülkeler son on yıldır finanasal krizler yaşamaktadırlar. Dünyada son on yıldır yaşanan en önemli finansal krizler 1994-95 Latin Amerika Finansal Krizi, 1992 İngiltere ( ERM ) Krizi, 1998 Rusya Ekonomik Krizi, 1996-97 Asya Krizi, ve 2000-2001 Türkiye Finansal Krizidir. Bu krizler sadece yaşandıkları ülkeleri değil dünyanın geniş bölgelerini de etkileri altına almışlardır.Bu da finansal piyasalardaki globalleşmenin bir sonucudur. Sonuç olarak finansal liberalizasyon ticari liberalizasyon gibi düşünülmemelidir.Finansal piyasalar kontrol altına alınmalı ve bazı uluslararası düzenlemeler olmalı ve finansal akışlar şimdikinden daha yavaş olmalıdır.

The economic recession, which started at the beginning of the 1970's caused important structural changes in the world economy. This structural changes created the necessity of carrying out the economical activities under more free regime than it was before. This process caused financial liberalisation and financial deregulation all over the world. In developing countries financial deregulation was made before providing macroeconomic balances. Therefore developing countries have been experiencing financial crises for the last ten years. Most important financial crises in the world, which where experienced for the last ten years, are 1994-95 Latin American Financial Crises, 1992 England ( ERM ) Crises, 1998 Russian Economic Crises, 1996-97 Asian Crises and 2000-2001 Turkey Financial Crises. These crises didn't effect only the countries, in which they are appeared, also they effected very wide area of the world. This is the reason of globalisation of the financial markets. As a result the financial liberalisation should not be considered like the commercial liberalisation. Financial activities must be put under control and there must be some international regulation, and financial flows must be more slow than they are.
Keywords: Asya_Ekonomik Durum; Ekonomi-Türkiye